Stunting Incidence in Infant Related to Mother’s History During Pregnancy - Wati, Erna Kusuma; Wahyurin, Izka Sofiyya; Sari, Hesti Permata; Zaki, Ibnu; Dardjito, Endo (KEMAS: Jurnal Kesehatan Masyarakat, 2022)
Stunting in an infant aged under two years old will affect the health and well-being of the children in the future. Banyumas Regency has 10 stunting locus villages with various nutritional problems that could lead to the incidence of stunting. Diet, nutritional status, and mother’s history during pregnancy will affect stunting in infants aged under two. This study aims to determine the relationship between the incidence of stunting in under-two infants related to parenting styles and mother’s history during pregnancy in stunting locus villages in Banyumas Regency. This study used a case-control design using a total sampling technique with 181 respondents. This type of data was collected through interviews using a questionnaire to mothers of the infants aged under two. While the measurement of body height and weight of under-five children was derived from the latest weighing data conducted by research enumerators using infatometers and digital baby scales. There was no relationship between maternal age (p = 0.21), birth spacing (p = 0.63), nutritional status (p = 0.40) with the incidence of stunting, and there was a significant relationship between maternal parenting styles and the incidence of stunting (p = 0.04).